The Differences in the implementation of physical education (pe) planning containing 21st-century skills based on period of work and gender - Amat Komari; Hari Yuliarto; Muhamad Nanang Solikhin; Yanuar Rachman Sadewa; Hendra Setyawan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This research aims to determine the implementation of PE planning incorporating 21st-century skills based on the length of service and gender of junior high school teachers in Yogyakarta. This research was conducted using a 2 x 2 factorial design with length of service and gender as factor variables, while the implementation of PE planning contains 21st-century skills as the dependent variable. The sample in this study was 68 junior high school PE teachers with a working period of 1 - 17 years and 18 - 32 years with male and female gender. The sampling technique uses probability sampling technique. Data were collected through questionnaires distributed to PE teachers. Data were analyzed using descriptive statistics and inferential. This research concludes that the first hypothesis shows no difference in the implementation of PE planning containing 21st-century skills when viewed from the work period. The mean difference in the performance of PE planning having 21st-century skills based on years of service is minimal, and it can be said that the implementation of PE planning containing 21st-century skills among teachers between working periods 1-17 and 18-32 tends to be the same. The second hypothesis shows no difference in the implementation of PE planning containing 21st-century skills regarding gender. The mean difference in the performance of PE planning having 21st-century skills based on gender is minimal. It can be said that the implementation of PE planning containing 21st-century skills for male and female teachers tends to be the same. The third hypothesis shows an interaction between length of service and gender in determining the implementation of PE planning containing 21st-century skills. This means that length of service and gender together influence the achievement of implementing PE planning and having 21st-century skills among junior high school teachers. This research recommends that each school's PE planning formulation team be assigned to competent teachers with sufficient teaching experience and consider gender in certain conditions and situations in each school.